Gender Differences in Risk Taking Among Entrepreneurs : Case on Small Medium Enterprise in Malang: English - Iin Agustina; Hafid Aditya Pradesa (Warmadewa Management and Business Journal (WMBJ), 2020)
Risk taking considered as one important dimension of entreprenurial orientation. This research aims to study gender differences on risk taking among entrepreneur. The overall objective of this research is to highlight the link between gender difference in risk taking when managing small business. Independent Sample T-Test and Confirmatory Factor Analysis was used to explore the phenomenon about whether there is differences in perception among male and female entrepreneur. Descriptive statistic reveals that female entrepreneur scored higher than the male entrepreneur on four of six indicator of risk taking. Eventhough there is no statistical differences in risk taking between male and female entrepreneur is small and the percentage of variance explained is low, there are significant differences in how male and female entrepreneur reflect their risk taking perception found in this study. Overall, these recommendations should help researchers to design and use more relevant risk-taking measures.Conclusions drawn from this study might be useful to better understand the use of risk taking model in entrepreneurial context.